The Association Between Food Addiction and Weight Status in School-Age Children and Adolescents - Wang, Dan; Huang, Ke; Schulte, Erica; Zhou, Wanying; Li, Huiwen; Hu, Yuzheng; Fu, Junfen (Frontiers in Psychiatry, 2022)
Background: The association between food addiction (FA) and weight status in children and adolescents remains poorly understood. This study aimed to elucidate the association between FA and weight status using the validated Chinese version of the dimensional Yale Food Addiction Scale for Children 2.0 (dYFAS-C 2.0). Methods: Participants were enrolled from clinic visitors for regular physical check in a children’s hospital. The dYFAS-C 2.0 was translated into Chinese and validated using reliability and validity tests. The participants’ body mass index Z score (BMIZ) and waist to-height ratio (WHtR) were used to characterize weight status. The FA severity was assessed using the translated dYFAS-C 2.0. Results: Among the 903 children and adolescents enrolled, 426 (47.2%) completed the survey (277 [65%] females and 149 [35%] males). The Cronbach’s α of translated dYFAS-C 2.0 was 0.934, and confirmatory factor analysis indicated an acceptable model fit. FA correlated positively with BMIZ and WHtR in the whole sample after adjusting for the effect of gender (P < 0.001). Further analyses showed that the correlation remained significant in participants with BMIZ > 1 (P = 0.006) but not in those with BMIZ ≤ 1 (P = 0.220). However, the correlations between FA and WHtR were statistically significant in both participants with or without abdominal obesity (P < 0.05). The FA could explain 12.1% and 15.8% of variance in BMIZ and WHtR, respectively. The corresponding cut-off points of FA for excessive weight risk were 0.7 (BMIZ) and 0.4 (WHtR). Conclusions: The dYFAS-C 2.0 has good reliability and validity in the Chinese population. FA is associated with weight status characterized by BMIZ and WHtR, especially in participants with BMIZ > 1 and in those with abdominal obesity.